Between Recogimientos, Vaccinations and Printing Presses: The Government of Toribio Montes and the Ways of Exercising Power in a Post-Revolutionary Context (Quito, 1812-1817) - Naranjo Robles, Heidi Yazmín (2024)
This article constitutes an initial approach to the government of Torivio Montes as president of the Audiencia of Quito. What is considered here are certain ways in which Montes exercised power in the aftermath of an insurgent process (the Quito Revolution from 1809 to 1812). Like other royal officials, Montes participated in a certain ideal which had developed in the Spanish Monarchy during the 18th century: that governing meant above all guaranteeing order (the proper arrangement of things) in the kingdom. To examine the ways in which Montes tried to put that ideal into practice, two things are carried out: on the one hand, a rereading of research on this royal official and the independence process of Quito; on the other hand, a review of documentation produced by him and certain collaborators of his.